"تقييم مدى استجابة المؤسسات الاقتصادية في الجزائر للمسؤولية الاجتماعية – دراسة العينة من المؤسسات القطاع الخاص –" - هاجر, براهيمي; غفران, بكاري; تهاني, العمامرة; مريم, بالهادف (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة إلى تقييم مدى استجابة المؤسسات الاقتصادية للمسؤولية الاجتماعية بأبعادها (المسؤولية الخيرية، المسؤولية الأخلاقية، المسؤولية القانونية، المسؤولية الاقتصادية) دراسة عينة من المؤسسات الاقتصادية بولاية الوادي. ولتحقيق أهداف هذه الدراسة تم توزيع 140 استبيانا على العامليين لدى مجموعة من المؤسسات الصناعية والخدمية، المتواجدة في مناطق مختلفة بولاية الوادي، وقد بلغ عدد المؤسسات التي تمكنا من زيارتها 8 مؤسسات، إلا أنه قد تمتم استرجاع 123استمارة، نظرا لعدم استجابة وتعاون بعض المسيرين؛ وتم معالجة البيانات من خلال برنامج التحليل الإحصائي SPSS V25. توصلت الدراسة إلى مجموعة من النتائج أهمها أنه مستوى استجابة المؤسسات الاقتصادية محل الدراسة للمسؤولية الاجتماعية من خلال أبعادها الأربعة: البعد الخيري؛ البعد الأخلاقي؛ البعد القانوني؛ البعد الاقتصادي هو مرتفع حسب إجابات عينة الدراسة، كما تبين من خلال نتائج اختبار الفرضية الرئيسية الثانية أنه يوجد اختلاف في مستوى استجابة المسؤولية الاجتماعية في المؤسسات محل الدراسة تبعا لاختلاف قطاع النشاط. ""This study aims to assess the extent to which economic institutions respond to social responsibility in its dimensions (charitable responsibility, moral responsibility, legal responsibility, economic responsibility) to study a sample of economic institutions in El Oued state. To achieve the objectives of this study, 140 questionnaires were distributed to workers in a group of industrial and service establishments located in different regions in the state of El Oued. The data was processed through the statistical analysis program SPSS V25. The study reached a set of results, the most important of which is the level of response of the economic institutions under study to social responsibility through its four dimensions: the charitable dimension; the ethical dimension; legal dimension; The economic dimension is high according to the answers of the study sample, as it was found through the results of the second main hypothesis test that there is a difference in the level of social responsibility response in the institutions under study according to the different sector of activity."
ماستر ادارة اعمال
Keywords: المؤسسة الاقتصادية، المسؤولية الاجتماعية، iso; economic institution, social responsibility, iso